2011
DOI: 10.1016/j.clinph.2010.08.016
|View full text |Cite
|
Sign up to set email alerts
|

The theoretical model of theta burst form of repetitive transcranial magnetic stimulation

Abstract: Objective-Theta burst stimulation, a form of repetitive transcranial magnetic stimulation, can induce lasting changes in corticospinal excitability that are thought to involve long-term potentiation/depression (LTD/LTD)-like effects on cortical synapses. The pattern of delivery of TBS is crucial in determining the direction of change in synaptic efficiency. Previously we explained this by postulating (1) that a single burst of stimulation induces a mixture of excitatory and inhibitory effects and (2) those eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
170
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(190 citation statements)
references
References 54 publications
8
170
2
1
Order By: Relevance
“…Huang et al showed that two TBS modalities have opposite effects on motor cortex excitability reminiscent of LTP and LTD (37). The iTBS of 600 pulses at 80% AMT produce a facilitatory effect for 15 minutes, whereas cTBS of 300 or 600 pulses suppress MEP amplitude for 20 or 60 minutes, respectively (46). Other studies of iTBS and cTBS showed similar results.…”
Section: Cortical Plasticity Induced By Tmssupporting
confidence: 65%
“…Huang et al showed that two TBS modalities have opposite effects on motor cortex excitability reminiscent of LTP and LTD (37). The iTBS of 600 pulses at 80% AMT produce a facilitatory effect for 15 minutes, whereas cTBS of 300 or 600 pulses suppress MEP amplitude for 20 or 60 minutes, respectively (46). Other studies of iTBS and cTBS showed similar results.…”
Section: Cortical Plasticity Induced By Tmssupporting
confidence: 65%
“…According to Huang et al, continuous TBS, as it was used in our study, tends to produce long-term-depression-like results. 36 From a practical point of view, it is noteworthy that naming improvements could be achieved by means of the simple stimulation localization procedure using the 10 -20 electroencephalogram system. This suggests that, at least for clinical purposes, a neuronavigation system for TMS coil positioning is not pivotal.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al showed that TBS seems to be able to induce plastic changes in cortical synapses in a long-term potentiation or long-term depression-like fashion. 19,36 In particular, they assume that the processes leading to long-term depression depend on the amount of Ca2ϩ entry, whereas the processes leading to long-term potentiation depend on the rate of Ca2ϩ entry. According to Huang et al, continuous TBS, as it was used in our study, tends to produce long-term-depression-like results.…”
Section: Discussionmentioning
confidence: 99%
“…The RMT was assessed by sequentially increasing the intensity until five out of ten MEPs (peak-to-peak) of at least 50 mV were registered. In line with current safety standards 35 , we employed an inhibitory cTBS as well as a facilitatory iTBS protocol identical to that in Huang et al 13 TBS consisted of bursts containing three pulses of 50 Hz at an intensity of 70% RMT repeated at 200-ms intervals (that is, at 5 Hz frequency). During each TBS session, 600 pulses were applied.…”
Section: Methodsmentioning
confidence: 99%
“…Continuous theta burst stimulation (cTBS) and intermittent TBS (iTBS) have been shown to induce opposing effects in neural circuits 11,12 , as they transiently inhibit and facilitate neural dynamics, respectively [11][12][13] . In three sessions, we applied cTBS, iTBS or shamTBS to the rIFG of healthy adult subjects.…”
mentioning
confidence: 99%